Determinants of academic startups' orientation toward international business expansion - Shinya Suzuki; Hiroyuki Okamuro (Administrative Sciences, 2017)
This study explores the determinants of academic startups' orientation toward international business expansion, focusing on their technological capabilities, availability of public support, the regional characteristics of their locations, and the research standards of their parent universities. Using unique survey data on 448 academic startups in Japan and by estimating an ordered logit model, we find that academic startups are strongly oriented toward expanding their businesses internationally if they have strong technological capabilities, receive public support, are established in regions with a high ratio of exporting small firms, or are affiliated with a parent university with an excellent research reputation.
Keywords: 350; academic startups; international business expansion; public support